EVALUASI PENGGUNAAN ANTIBIOTIK DENGAN METODE GYSSENS PADA PASIEN DEMAM TIFOID ANAK DI INSTALASI RAWAT INAP RSUP Dr. SITANALA TAHUN 2019-2021 - Megawati, Sefi; Nuraini, Nuraini; Carolina, Febby (Jurnal Insan Farmasi Indonesia, 2023)
Typhoid fever is a disease caused by bacteria and its treatment requires antibiotics. Antibiotic-resistant bacteria can grow as a result of improper use of antibiotics. The purpose of this study was to determine the rational usage pattern and percentage of antibiotic drug use according to the Gyssens method. This non-experimental study employed retrospective data collecting from the medical records of children treated for typhoid fever at the Dr. Sitanala in 2019–2021 and used the Gyssens technique for analysis. According to the study's findings, 28 patients (46.67%) were classified as irrational, whereas 32 patients (53.33%) were considered rational (category 0). In this study, it can be concluded that the use of antibiotics used in typhoid fever patients, namely ceftriaxone (82,54%), cefotaxime (14.29%), and cefixime (3.17%) with the intravenous route of administration (96.83%) and orally (3.17%). Irrational use of antibiotics included Gyssens category V (antibiotics are not needed) (1.67%), category IVC (there are cheaper antibiotics) (11,86%), category IIIB (the duration of giving antibiotics are too short) (30,51%), category IIA (not the right doses) (20,34%), and category I (not on time to give antibiotics) (18.64%).